Economic Implications of German Unification for the Federal Republic and the Rest of the World - Masson, Paul (IMF Working Papers; Working Paper ;, 1990)
The economic effects of German unification are first discussed in the context of a global saving/investment model. Next, simulations of MULTIMOD are presented, suggesting for the FRG an initial increase in long-term real interest rates equal to 3/4 of a percentage point, increased output, a temporary half-point rise in inflation, a modest real appreciation of the deutsche mark, and a reduction of the (combined GDR and FRG) current account surplus equal to 2 percent of GNP. Effects on the rest of the world seem to be relatively small. Different policies are examined within the EMS, and other simulation studies are surveyed.